Morpho-Physiological Responses of Malabayabas (Tristaniopsis decorticata (Merr.) Peter G. Wilson & J.T. Waterh.) Seedlings Inoculated with Arbuscular Mycorrhizal Fungi - Corbita, Victor Lobrigas; Combalicer, Marilyn Sabalvaro; Manalo, Mutya Ma Quintos; Galang, Marco Aragones; Maldia, Lerma San Jose (Jurnal Sylva Lestari, 2024)
Malabayabas (Tristaniopsis decorticata (Merr.) Peter G. Wilson & J.T. Waterh.) of the Myrtaceae family is a vulnerable endemic tree species in the Philippines. Poor development and low regeneration rates of seedlings in their natural habitats have led to a considerable population decline of the species. This study aimed to determine the morphological and physiological growth responses of T. decorticata seedlings in different soil media inoculated with arbuscular mycorrhizal fungi applied once at a rate of 5 g per seedling for the entire duration of the experiment. Morphological parameters were collected using conventional methods, while physiological parameters were measured using LI-6400 XT Portable Photosynthesis System. Results of the study revealed that the morphological growth of seedlings was generally better in Bantay soil regardless of treatments than in Lipa soil. Interestingly, the net photosynthesis, transpiration rate, and water-use efficiency were generally higher in Lipa unsterilized soil inoculated with arbuscular mycorrhizal fungi. However, this study can not yet confirm the percentage of Arbuscular Mycorrhizal Fungi (AMF) root colonization. Thus, further research must be conducted to determine the AMF root colonization and identify potential indigenous mycorrhizal fungi in both soil media. Keywords: arbuscular mycorrhizal fungi, endemic, net photosynthesis, transpiration rate, Tristanipsis decorticata